Pelatihan Soft Skill dan Manajemen Konflik Bagi Perangkat Desa dalam Meningkatkan Kinerja Pelayanan Publik di Kelurahan Sidodadi, Bandar Lampung - Chandra, Dharnita; Suri, Dharlinda; Yuliana, Yuliana; Maulana, Dede Yusuf (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Effective and responsive public service at the village or sub-district level relies heavily on human resource capacity, particularly in mastering soft skills and conflict management. In Sidodadi Sub-district, Bandar Lampung, public service delivery still faces various challenges, such as miscommunication among staff, confusing service procedures for citizens, and weak cross-sectoral coordination. These issues are exacerbated by entrenched hierarchical work culture based on seniority, which hinders synergy and efficiency in providing integrated services. To address these problems, a community service program (PKM) was implemented in the form of soft skills and conflict management training for local government personnel. The method included partnership approval and coordination, problem identification through observation and interviews, development of need-based training modules, delivery of interactive sessions, and evaluation using pre-test and post-test instruments. A total of 25 staff members from different units of the sub-district participated in the program. Evaluation results showed a significant improvement in participants’ understanding, with the average score increasing from 62.4 to 84.6 after the training (an increase of 35.6%). As many as 88% of participants improved by more than 15 points, and 96% expressed readiness to promote cross-functional collaboration without emphasizing seniority. This training has proven effective in fostering behavioural change toward more professional, synergistic, and citizen-oriented public service.